Calculation evaluation of multiplying properties of LWR with thorium fuel; Journal of Physics: Conference Series; Vol. 781 : Nuclear Reactor Physics 2016 (ICNRP-2016) - Shamanin I. V. Igor Vladimirovich; Grachev V. M. Viktor Mikhaylovich; Knyshev V. V. Vladimir Vladimirovich; Bedenko S. V. Sergey Vladimirovich; Novikova N. G. Natalia Gennadievna (2017, 2017)
Title screen